2020
DOI: 10.3390/rs12244142
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Prediction with Multi-Modal Data and Deep Neural Networks

Abstract: Air pollution is becoming a rising and serious environmental problem, especially in urban areas affected by an increasing migration rate. The large availability of sensor data enables the adoption of analytical tools to provide decision support capabilities. Employing sensors facilitates air pollution monitoring, but the lack of predictive capability limits such systems’ potential in practical scenarios. On the other hand, forecasting methods offer the opportunity to predict the future pollution in specific ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 58 publications
0
43
0
Order By: Relevance
“…Benefiting from the development of high-performance computers and the availability of large-scale training data [36,37], deep learning-based approaches [38][39][40][41] have attracted more and more attention. Among the typical deep architectures, CNN provides a strong ability of feature extraction and yield significant performance improvement on scene classification.…”
Section: The Deep Learning-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefiting from the development of high-performance computers and the availability of large-scale training data [36,37], deep learning-based approaches [38][39][40][41] have attracted more and more attention. Among the typical deep architectures, CNN provides a strong ability of feature extraction and yield significant performance improvement on scene classification.…”
Section: The Deep Learning-based Methodsmentioning
confidence: 99%
“…Zhao et al [51] developed a multitask learning framework that improved the discrimination ability of the model features by taking advantage of different tasks. Kalajdjieski et al [41] applied a series of deep CNNs together with other sensor data for the classification of air pollution.…”
Section: The Deep Learning-based Methodsmentioning
confidence: 99%
“…The same approach can be used in cities and other areas. Taking preventive measures could decrease the influence on the air quality upfront and prevent or minimize the citizens' exposure to air with hazardous pollution [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage of development, traditional machine learning methods have been used for scene classification tasks, such as support vector machine and bag of words [2,3]. Recently, deep learning methods have been proven to be effective for extracting image features [4][5][6][7][8], and many studies have demonstrated effective scene classification performance with the help of deep learning from various novel perspectives including self-supervised learning [9], data augmentation [10], feature fusion [11][12][13][14][15], reconstructing networks [16][17][18][19][20][21][22][23], integration of spectral and spatial information [24], balancing global and local features, refining feature maps through encoding method [25], adding a new mechanism [26,27], as well as introducing a new network [28], open set problem [29], and noisy label distillation [30]. However, a lack of annotated data has restricted the development of deep learning methods in scene classification due to the high cost of annotating data.…”
Section: Introductionmentioning
confidence: 99%